Pengaruh Motivasi Dan Kepribadian Terhadap Organizational Citizenship Behavior (OCB) Guru SMA Pada SMA Negeri 1 Tenggarong - Sugeng Raharjo (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
The present study aims to determine the influence of motivation and personality on organizational citizenship behavior (OCB) of teachers SMA Negeri 1 Tenggarong and to determine and assess the most dominant variable effect on the OCB. The research was conducted at SMA Negeri 1 Tenggarong the target population was teachers who works in SMA Negeri 1 Tenggarong. The sample used for this study were 52 respondents to the techniques of data collection using questionnaires.Based on the results of research and data analysis, test the first hypothesis which states motivational effect on organizational citizenship behavior, acceptable. This is evidenced by the t value ? t table (2., 760 ? 2.008). Then the second hypothetical test that says personality affects organizational citizenship behavior is acceptable as evidenced by the t value ? t table (3.723 ? 2.008). As for the third hypothesis which stated motivation most dominant influence on OCB rejected. It is based on the calculation of correlations where the coefficients personality is 0.494 or 49.4% and the coefficient of motivation is 0.400 or 40% so that it can be explained that the most influential personalities of the Organizational citizenship behavior dominant.Keywords : Motivation, Personality dan Organizational Citizenhsip Behavior (OCB)